Central noradrenaline transporter availability in highly obese, non-depressed individuals. - Hesse, Swen; Becker, Georg-Alexander; Rullmann, Michael; Bresch, Anke; Luthardt, Julia; Hankir, Mohammed; Zientek, Franziska; Reißig, Georg; Patt, Marianne; Arelin, Katrin; Lobsien, Donald; Müller, Ulrich; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2017)
Purpose: The brain noradrenaline (NA) system plays an important role in the central nervous control of energy balance and is thus implicated in the pathogenesis of obesity. The specific processes modulated by this neurotransmitter which lead to obesity and overeating are still a matter of debate. Methods: We tested the hypothesis that in vivo NA transporter (NAT) availability is changed in obesity by using positron emission tomography (PET) and S,S-[C]O-methylreboxetine (MRB) in twenty subjects comprising ten highly obese (body mass index BMI > 35 kg/m), metabolically healthy, non-depressed individuals and ten non-obese (BMI < 30 kg/m) healthy controls. Results: Overall, we found no significant differences in binding potential (BP) values between obese and non-obese individuals in the investigated brain regions, including the NAT-rich thalamus (0.40 ± 0.14 vs. 0.41 ± 0.18; p = 0.84) though additional discriminant analysis correctly identified individual group affiliation based on regional BP in all but one (control) case. Furthermore, inter-regional correlation analyses indicated different BP patterns between both groups but this did not survive testing for multiple comparions. Conclusions: Our data do not find an overall involvement of NAT changes in human obesity. However, preliminary secondary findings of distinct regional and associative patterns warrant further investigation.